The Hazards of Debt: Rollover Freezes, Incentives, and Bailouts - Cheng, Ing-Haw; Milbradt, Konstantin (Review of Financial Studies, 2012)
We investigate the trade-off between incentive provision and inefficient rollover freezes for a firm financed with short-term debt. First, debt maturity that is too short-term is inefficient, even with incentive provision. The optimal maturity is an interior solution that avoids excessive rollover risk while providing sufficient incentives for the manager to avoid risk-shifting when the firm is in good health. Second, allowing the manager to risk-shift during a freeze actually increases creditor confidence. Debt policy should not prevent the manager from holding what may appear to be otherwise low-mean strategies that have option value during a freeze. Third, a limited but not perfectly reliable form of emergency financing during a freeze—a “bailout”—may improve the terms of the trade-off and increase total ex ante value by instilling confidence in the creditor markets. Our conclusions highlight the endogenous interaction between risk from the asset and liability sides of the balance sheet.